Insecurity and the State of the Nation - IKENGA, Francis A.; E. AGAH, Benjamin (International Journal of Psychosocial Rehabilitation, 2020)
Nigerian’s chequered political history is currently bedevilled by myriads of security challenges ranging from Boko Haram insurgency, kidnappings and hostage takings, herdsmen and farmers’ clashes, organized armed robberies, ethnic militias, threats of secession by dissatisfied groups within the Nigerian state, banditry, home torture centres masterminded by clerics, human trafficking, massive decline in roads infrastructures across the nation, corruption and electoral violence. The frequency and intensity of these challenges are on the increase on a daily bases with no solution from the political leadership which tends to affirm the fact that Nigeria is dwindling towards the status of a failed state. The general objective of this paper is to examine the security challenges facing the country with a view to proffering lasting solutions that will enable us change the dynamics. Using the historical and survey methods of data collection with the political economy approach, the study examined the issues of insecurity in the country. It was found out that these problems bedevilling the country are elite driven deriving mainly from poor political leadership and the poor mindsets of our political elites to embark on what is needful to move the country forward. Secondly, it was observed that security has been compromised by security officials, hence its increasing intensity. Thirdly, it was also noted that unemployment and poverty are also major causes of the insecurity problem. The study is expected to contribute to knowledge production in the following ways: Firstly, it will bring to the fore strategies that will bring to an end the problems of insecurity in the country. Secondly, it will provide feasible and implementable policies that will check the early occurrence of some of these challenges with a view to detecting them early for appropriate action.